Utilizing the Quizizz Application to Improve Students’ Vocabulary Mastery at Senior High School - Frisca Oktaviany; Sujarwo; Muhamad Yahrif (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2026)
This study aims to determine how effective the Quizizz application is in increasing student vocabulary at SMA Negeri 23 Makassar. This study used a quasi-experimental method. Two classes were selected as samples: one experimental class that used Quizizz to teach vocabulary and one control class that used conventional methods. Pre-test, post-test, and questionnaire were used in this study. Data were analyzed using descriptive and inferential statistics using the SPSS 25 program. The results showed a significant increase in students' vocabulary mastery in the experimental class compared to the control class. The average score of the experimental group increased from 58.42 in the pre-test to 87.67 in the post-test. Meanwhile, the control class increased from 57.61 to 66.33. Findings from the independent t-test showed a significant difference between the post-test scores of both groups (sig. <0,05), which confirmed the effectiveness of Quizizz as an interactive learning medium. In conclusion, Quizizz app contributed positively in improving students’ vocabulary mastery and engagement in English learning.